COMPARISON OF SURGICAL SITE INFECTION IN PATIENTS UNDERGOING SKIN CLOSURE WITH STAPLES VS. SUTURES IN CLEAN ELECTIVE SURGERIES - AFSAR, B; ANWER, I; TARAR, AJ; SIKANDAR, S; GHAFFAR, H; KHAN, MU (Biological and Clinical Sciences Research Journal, 2024)
Thyroidectomy is a common surgical procedure with various techniques for wound closure, including dermal staples and intradermal suturing. Each method has potential advantages and disadvantages, particularly in terms of wound complications, cosmetic outcomes, and postoperative pain. Understanding which technique offers better outcomes in these areas can guide surgeons in selecting the most appropriate method for skin closure after thyroidectomy. Objective: To compare wound complications, cosmetic outcomes, and pain scores between skin closure with dermal staples and intradermal sutures in patients undergoing thyroidectomy. Methods: A prospective study was conducted in the Surgical Department of Sheikh Zayed Hospital, Lahore, from August 2023 to August 2024. The study included 100 adult patients undergoing thyroidectomy for thyroid disease. The patients were randomly divided into two groups: Group A (n=50) received wound closure with dermal staples, and Group B (n=50) received intradermal suturing. Postoperative assessments were conducted at 1, 4, 12, and 24 weeks to evaluate wound complications, cosmetic outcomes, and pain scores. Cosmetic outcomes were measured using the Stony Brook Scar Evaluation Scale and Manchester Scar Scale. Pain was assessed using the Visual Analog Scale (VAS). Results: No surgical site infections were reported in either group. At the 24-week follow-up, cosmetic outcomes measured by the Stony Brook Scar Evaluation Scale were significantly better in Group A (4.12 ± 1.0) compared to Group B (3.32 ± 1.17) (p=0.027). Similarly, the Manchester Scar Scale score was higher in Group A (7.83 ± 1.34) than in Group B (9.20 ± 2.26) (p=0.033), indicating better cosmesis with staples. However, pain scores were significantly higher in Group A than in Group B both immediately after surgery and at the 4- and 12-week follow-ups. Conclusion: The use of dermal staples in thyroidectomy demonstrated better cosmetic outcomes and wound healing compared to intradermal suturing. However, patients who received staples experienced significantly more postoperative pain. While dermal stapling is a safe and effective alternative for skin closure, further studies with larger populations are necessary to corroborate these findings and guide clinical practice.